Penguatan Identitas dan Pemasaran Digital pada UMKM Warung Seribu Berkah Mbak Siti Bagus Melalui Program Kuliah Kerja Usaha - Anisa Rosiana Anggraheni; Sabti Ramadhina; Muhammad Zaim Mustofa; Dian Anita Sari (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Mbak Siti Bagus's Warung Seribu Berkah UMKM is located in the Karang Jahe Beach tourist area, Punjulharjo Village, Rembang District, Rembang Regency, Central Java. Within 10 years of running the business, the UMKM experienced obstacles in developing the business, namely branding that was not optimal, which was indicated by: 1) Not having a business identity; 2) the location of the UMKM was difficult to identify with other UMKM; and 3) the business did not have an online marketing channel. From these obstacles, the Business Work Lecture (KKU) Team provided assistance with a program to maximize branding by: 1) Creating a logo design for cup packaging; 2) Creating a logo on the packaging; 2) Creating proof of payment receipts, 3) Creating Google Maps aimed directly at the UMKM stall, and 4) Creating social media accounts in the form of TikTok and Instagram. The KKU implementation method includes: 1) Pre-survey to the MSME Location, 2) Identifying problems in the MSME Warung Seribu Berkah Mbak Siti Bagus, 3) Program preparation, 4) Program implementation, 4) Mentoring, 5) Evaluation. The program results obtained are as follows: 1) MSMEs have a unique logo for cup packaging, 2) MSMEs already have a note to add up orders, 3) MSMEs already have Google Maps which are directly centralized in the MSME stall, and 4) MSMEs have social media accounts to facilitate marketing